2015
DOI: 10.1371/journal.pone.0123137
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Salivary Function and Oral Microbiota of Radiation Caries-Free People with Nasopharyngeal Carcinoma

Abstract: Radiation caries have been reported to be correlated with radiotherapy-induced destruction of salivary function and changes in oral microbiota. There have been no published reports detailing patients who have remained radiation caries-free following radiotherapy for nasopharyngeal carcinoma. The aim of this study was to investigate the relationship between salivary function, oral microbiota and the absence of radiation caries. Twelve radiation caries-free patients and nine patients exhibiting radiation caries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 60 publications
1
25
0
7
Order By: Relevance
“…Notably, authors did not detect any significant decrease in pH value and buffering capacity of the stimulated saliva when compared with normal values. Zhang et al (2015) reported the quantity of Streptococcus mutans and Lactobacilli were same in both the radiation caries free patients and radiation caries patients. The results were in contradiction with previously published reports possibly because all the participants in their studies had not been treated by radiotherapy and had healthy salivary function and their data showed only a weak correlation between oral microbial diversity with the absence of radiation caries.…”
Section: Dental/radiation Cariesmentioning
confidence: 90%
See 1 more Smart Citation
“…Notably, authors did not detect any significant decrease in pH value and buffering capacity of the stimulated saliva when compared with normal values. Zhang et al (2015) reported the quantity of Streptococcus mutans and Lactobacilli were same in both the radiation caries free patients and radiation caries patients. The results were in contradiction with previously published reports possibly because all the participants in their studies had not been treated by radiotherapy and had healthy salivary function and their data showed only a weak correlation between oral microbial diversity with the absence of radiation caries.…”
Section: Dental/radiation Cariesmentioning
confidence: 90%
“…The richness and diversity of oral ecology decreased with increased radiation dose which was gradually restored with time. Zhang et al (2015) Licensed Under Creative Commons Attribution CC BY salivary function in irradiated patients does not recover fully after 12-36 months, although the pH value and buffering capacity of saliva returns to normal after one year or more following intensity modulated radiation therapy. Further, it was concluded that population-based long term studies are required to reveal the factors for the absence of radiation caries.…”
Section: Changes In Oral Cavity Microflora After Radiotherapymentioning
confidence: 99%
“…Most studies that have evaluated the microbiota of individuals experiencing significant, chronic reductions in salivary flow (known as hyposalivation) have done so largely without regard for habitat structure in the mouth; most have used rinsing samples. [49][50][51][52][53][54][55] Other work only sampled a single supragingival surface. 56 Of the studies that did sample multiple sites, such as the maxillary and mandibular molars, samples were pooled before analysis, [57][58][59] or summary data were reported for whole mouths rather than for specific sites.…”
Section: Spatial Patterns Of Dental Caries and The Supragingival MImentioning
confidence: 99%
“…Most prior studies that have evaluated the microbiota of individuals experiencing significant, chronic reductions in salivary flow (known as hyposalivation) have done so largely without regard for habitat structure in the mouth; most have used rinsing samples [49][50][51][52][53][54][55] . Other work only sampled a single supragingival surface 56 .…”
Section: Spatial Patterns Of Dental Caries and The Supragingival Micrmentioning
confidence: 99%